Hadith #344 - Sahih Muslim - Masruq (Sahih Muslim)
I was resting at (the house of) ‘A’isha that she said: O Abu ‘A’isha (kunya of Masruq), there are three things, and he who affirmed even one of them fabricated the greatest lie against Allah. I asked that they were. She said: He who presumed that Muhammad (ﷺ) saw his Lord (with his ocular vision) fabricated the greatest lie against Allah. I was reclining but then sat up and said: Mother of the Faithful, wait a bit and do not be in a haste. Has not Allah (Mighty and Majestic) said:” A
Grade: Sahih

Hadith #346 - Sahih Muslim - Masruq (Sahih Muslim)
I asked ‘A’isha if Muhammad (ﷺ) had seen his Lord. She replied: Hallowed be Allah, my hair stood on end when you said this, and he (Masruq) narrated the hadith as narrated above. The hadith reported by Diwud is more complete and longer.
Grade: Sahih

Hadith #347 - Sahih Muslim - Masruq (Sahih Muslim)
I said to ‘A’isha: What about the words of Allah:” Then he drew nigh and came down, so he was at a distance of two bows or closer still: so He revealed to His servant what He revealed” (al-Qur’an, liii. 8-10)? She said: It implies Gabriel. He used to come to him (the Holy Prophet) in the shape of men; but he came at this time in his true form and blocked up the horizon of the sky.
Grade: Sahih

Hadith #1045 - Sahih Muslim - Masruq (Sahih Muslim)
It was mentioned before’A’isha that prayer is invalidated (in case of passing) of a dog, an ass and a woman (before the worshipper, when he is not screened). Upon this ‘A’isha said: You likened us to the asses and the dogs. By Allah I saw the Messenger of Allah (ﷺ) saying prayer while I lay on the bedstead interposing between him and the Qibla. When I felt the need, I did not like to wit to front (of the Holy Prophet) and perturb the Messenger of Allah (ﷺ) and quietly moved out from
Grade: Sahih

Hadith #1222 - Sahih Muslim - Masruq (Sahih Muslim)
Never did he (the Holy Prophet) say prayer after this in which I did not hear him seeking refuge from the torment of the grave.
Grade: Sahih

Hadith #1623 - Sahih Muslim - Masruq (Sahih Muslim)
He (the Holy Prophet) loved (that action) which one keeps on doing regularly. I said (to ‘A’isha): When did he pray (at night)? She replied: When he heard the cock crow, he got up and observed prayer.
Grade: Sahih

Hadith #3084 - Sahih Muslim - Masruq (Sahih Muslim)
I heard ‘A’isha (Allah be pleased with her) clapping her hands behind the curtain and saying: I used to weave garlands for the sacrificial animals of Allah’s Messenger (ﷺ) with my own hands, and then he (the Holy Prophet) sent them (to Mecca), and he did not avoid doing anything which a Muhritn avoids until his animal was sacrificed.
Grade: Sahih

Hadith #3562 - Sahih Muslim - Masruq (Sahih Muslim)
I do not mind if I give option to my wife (to get divorce) once, hundred times, or thousand times after (knowing it) that she has chosen me (and would never seek divorce). I asked ‘A’isha (Allah be pleased with her) (about it) and she said: Allah’s Messenger (ﷺ) gave us the option, but did it imply divorce? (It was in fact not a divorce; it is effective when women actually avail themselves of it.)
Grade: Sahih

Hadith #4750 - Sahih Muslim - Masruq (Sahih Muslim)
We asked ‘Abdullah about the Qur’anic verse:” Think not of those who are slain in Allah’s way as dead. Nay, they are alive, finding their sustenance in the presence of their Lord..” (iii. 169). He said: We asked the meaning of the verse (from the Holy Prophet) who said: The souls, of the martyrs live in the bodies of green birds who have their nests in chandeliers hung from the throne of the Almighty. They eat the fruits of Paradise from wherever they like and then nestle in these chan
Grade: Sahih

Hadith #5877 - Sahih Muslim - Masruq (Sahih Muslim)
We went to Abdullah b. ‘Amr when Mu’dwiya came to Kufa, and he made a mention of Allah’s Messenger (ﷺ) and said: He was never immoderate in his talk and he never reviled others. Allah’s Messenger (ﷺ) also said: The best amongst you are those who are best in morals. Uthman said: When he came to Kufa along with Mu’awiya… (The rest of the hadith is the same).
Grade: Sahih

Hadith #6176 - Sahih Muslim - Masruq (Sahih Muslim)
We used to go to Abdullah b. ‘Amr and talk to him, Ibn Numair said: One day we made a mention of Abdullah b. Mas’ud, whereupon he said: You have made mention of a person whom I love more than anything else. I heard Allah’s Messenger (ﷺ) as saying: Learn Qur’an from four persons: Ibn Umm ‘Abd (i. e. ‘Abdullah b. Mas’ud) he started from him-then Mu’adh b. Jabal and Ubayya b. Ka’b, then Salim the ally of Abu Hudhaifa.
Grade: Sahih

Hadith #6177 - Sahih Muslim - Masruq (Sahih Muslim)
We were in the company of Abdullah b ‘Amr that we made a mention of a hadith from Abdullah b. Mas’ud; thereupon he said: That is a person whose love ever remains (fresh in my heart) after I heard Allah’s Messenger (ﷺ) as saying: Learn Qur’an from four persons: Ibn Umm ‘Abd, i e. Abdullah b. Mas’ud and he started from his name-then Ubayy b. Ka’b and Mu’adh b Jabal. Zuhri did not make a mention of the words yaquluhu in his narration
Grade: Sahih

Hadith #6180 - Sahih Muslim - Masruq (Sahih Muslim)
They made a mention of Ibn Mas’ud before ‘Abdullah b. Amr, whereupon he said: He is a person whose love is always fresh in my heart after I heard Allah’s Messenger (ﷺ) as saying: Learn the recita- tion of the Qur’an from four persons: from Ibn Mas’ud, Salim, the ally of Abu Hudhaifa, Ubayy b. Ka’b, Mu’adh b. Jabal.
Grade: Sahih

Hadith #6233 - Sahih Muslim - Masruq (Sahih Muslim)
I visited ‘A’isha when Hassin was sitting there and reciting verses from his compilation: She is chaste and prudent. There is no calumny against her and she rises up early in the morning without eating the meat of the un- mindful. ‘A’isha said: But you are not so. Masruq said: I said to her: Why do you permit him to visit you, whereas Allah has said:” And as for him among them who took upon himself the main part thereof, he shall have a grievous punishment” (XXIV. ll)? Thereupon she
Grade: Sahih

Hadith #6892 - Sahih Muslim - Masruq (Sahih Muslim)
We were sitting in the company of Abdullah and he was lying on the bed that a person came and said: Abd Abd al-Rabmin, a story-teller at the gates of Kinda says that the verse (of the Qur’an) which deals with the” smoke” implies that which is about to come and it would hold the breath of the infidels and would inflict the believers with cold. Thereupon Abdullah got up and said in anger. O people, fear Allah and say only that which one knows amongst you and do not say which he does not know
Grade: Sahih

Hadith #6893 - Sahih Muslim - Masruq (Sahih Muslim)
I have left behind in the mosque a man who explains the Qur’an according to his personal discretion and he explained this verse:” So wait for the day when the Heaven brings a clear smoke.” He says that a smoke would come to the people on the Day of Resurrection anl it will withhold breath and they would be inflicted with cold. ‘Abdullah said: He who has knowledge should say something and he who has no knowledge should simply say: Allah is best aware. This reflects the understanding of a
Grade: Sahih